1999
DOI: 10.1073/pnas.96.11.6529
|View full text |Cite
|
Sign up to set email alerts
|

Dual pathways for regulation of root branching by nitrate

Abstract: Root development is extremely sensitive to variations in nutrient supply, but the mechanisms are poorly understood. We have investigated the processes by which nitrate (NO 3 ؊ ), depending on its availability and distribution, can have both positive and negative effects on the development and growth of lateral roots. When Arabidopsis roots were exposed to a locally concentrated supply of NO 3 ؊ there was no increase in lateral root numbers within the NO 3 ؊ -rich zone, but there was a localized 2-fold increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
582
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 606 publications
(623 citation statements)
references
References 50 publications
29
582
0
4
Order By: Relevance
“…Nitrate is one of the major nutrients known to act as a signal molecule in the regulation of root architecture through the regulation of primary root growth and by influencing the emergence and development of lateral roots (LR) Forde 1998, 2000;Zhang et al 1999;Tian et al 2008;Vidal et al 2010;Celis-Arámburo et al 2011). This effect is complicated due to the changes in root architecture caused by changes in root environment and their influence on plant physiology.…”
Section: Primary Nitrate Responsementioning
confidence: 99%
“…Nitrate is one of the major nutrients known to act as a signal molecule in the regulation of root architecture through the regulation of primary root growth and by influencing the emergence and development of lateral roots (LR) Forde 1998, 2000;Zhang et al 1999;Tian et al 2008;Vidal et al 2010;Celis-Arámburo et al 2011). This effect is complicated due to the changes in root architecture caused by changes in root environment and their influence on plant physiology.…”
Section: Primary Nitrate Responsementioning
confidence: 99%
“…Recent studies with Arabidopsis showed that a localized supply of NO 3 − stimulated lateral root elongation by 2-to 3-fold in the NO 3 − -rich zone and that even 0.1 mm NO 3 − (when the rest of the root received 0.01 mm) was sufficient to elicit the maximal response (Zhang et al, 1999). Unlike barley, but similar to maize (Sattelmacher and Thoms, 1995), the localized NO 3 − supply had no significant effect on lateral root initiation.…”
Section: Root Growth and Branchingmentioning
confidence: 99%
“…If the lateral roots were allowed to progress up to or beyond the point of emergence before the plants received the 50 mM NO 3 − treatment, there was no effect on their growth (Zhang et al, 1999), demonstrating that there is a very specific stage of lateral root development which is sensitive to the high rate of NO 3 − supply. These stunted lateral roots were only temporarily blocked: if the experiment was extended for a further 7 days or so many of them had matured and were elongating at normal rates.…”
Section: Root Growth and Branchingmentioning
confidence: 99%
See 1 more Smart Citation
“…The instantaneous root: shoot ratio in any individual plant is subjected to genetic, ontogenetic, and environmental control (Gedroc et al, 1996). The root systems of plants show highly plastic development because root systems develop by responding to the availability of phosphate and nitrate (Zhang et al, 1999). But, root systems originate from a primary root that develops during embryogenesis; that is, an intrinsic pathway (Malamy, 2005).…”
Section: Variation In Seed Size and Growth Processmentioning
confidence: 99%